ANALISIS PENGARUH BEBERAPA FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP HARGA SAHAM - Syahib Natarsyah (UGM, 2000)
This research is aimed at analyzing influence of several fundamental factors and systematic risk on stock price of consumption goods industries. The group of consumption goods industry has been chosen asresearch object considering that the products obstained are strategic consumption commodities badly needed by the society as a whole, in which are not only in the form of nutricious food and drink , but also medicines, health products, cosmetc and other household basic necessities.